SISTEM PENENTUAN GUDANG BERAS BERBASIS IOT MENGGUNAKAN METODE SAW PADA PLATFORM THINGSBOARD - Timbo Faritcan Parlaungan S.; Agus Sudrajat (STMIK SUBANG, 2020)
Determination of Rice Warehouse Storage System, Kasomalamg is a system that can assist officers in maintaining Rice Storage. There are several factors that can affect the quality of rice security, namely, temperature, humidity, and dust. Which can affect the quality of rice becomes moldy and fast ticking.The purpose of this study is to determine the durability of rice storage with the quality of temperature, humidity, and cleanliness of the room with different values. Data calculated using the Microcontroller with DHT11 Sensor to read temperature parameters and humidity parameters as well as dust sensors that can read the thickness of the dust based on the Internet of Things. Then the data is processed using the ranking method with Simple Addictive Weight (SAW) to determine the storage of rice with the highest calculation results as the best rice storage.